Islam dan Etnonasionalisme Tengku Hasan M. Tiro untuk Perjuangan Aceh Merdeka 1976-1998 - Al Maududdy, Avicenna; Usman, Usman; Abdullah, Munawiah; Ashri, Teuku Luthfi (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
Terinspirasi oleh kekayaan warisan budaya Aceh, merekonstruksi identitas Aceh atas dasar nasionalisme etnis. Ia merekonstruksi sejarah dan membangkitkan sentimen kolektif masyarakat Aceh untuk menyebarkan gagasannya. Cara berpikirnya memandang Islam sebagai salah satu komponen adat yang membentuk hukum adat Aceh atau dari sudut pandang politik Islam. Selanjutnya masyarakat Aceh ditampilkan sebagai fakta sejarah atau realitas kehidupan di masyarakat, dan Islam ditampilkan sebagai agama dengan prinsip-prinsip luhur bagi umatnya untuk melawan kejahatan. Kajian ini mengambil pendekatan politik dengan menyelidiki sejarah. Tujuan penelitian ini adalah untuk melihat pemikiran Tengku Hasan M. Tiro tentang Islam dan etnonasionalisme dalam konteks perjuangan Aceh Merdeka. Kajian ini menggunakan metodologi tinjauan pustaka yang memanfaatkan berbagai sumber, termasuk tulisan ilmiahnya. Evolusi masyarakat Aceh dalam perjuangan Aceh Merdeka akan dibahas dalam penelitian ini, beserta kepemimpinan Tengku Hasan M. Tiro dalam perjuangan tersebut, serta analisis pencampuran terhadap Islam dan etnonasionalisme serta pengaruhnya terhadap Aceh Merdeka.————————————————————————————————Inspired by the richness of Aceh's cultural heritage, reconstructing Aceh's identity on the basis of ethnic nationalism. Reconstructing history and arousing collective sentiments of the Acehnese people to spread their ideas. His way of thinking views Islam as one of the components of customs that form Aceh's customary law or from an Islamic political perspective. Furthermore, the Acehnese people are presented as historical facts or realities of life in society, and Islam is presented as a religion with noble principles for its people to fight against evil and injustice. This study takes a political approach by conducting historical investigations. The purpose of this study is to analyze Tengku Hasan M. Tiro's thoughts on Islam and ethnonationalism in the context of the struggle for Aceh's Independence. Literature study with literature analysis is a method of data collection for the purpose of this study. The data collected is then reviewed and then written into one complete article. How the Acehnese Revolution in the struggle for Aceh's Independence, how Tengku Hasan M. Tiro's leadership in the struggle, and why his views on Islam and his ideas of ethnonationalism influenced the struggle for Aceh's Independence will be discussed in this study. The ethnonationalist thought or also known as Acehnese Nationalism of Tengku Hasan M. Tiro which was mobilized in the struggle for Aceh Merdeka has defined the identity of the Acehnese nation in maintaining Aceh's sovereignty. Although there are different opinions about the purpose of establishing an independent Acehnese state, his efforts and beliefs are very beneficial for the continuity of Aceh's political life today.